Bone Fractures Numerical Analysis in a Femur Affected by Osteogenesis Imperfecta - Viridiana Ramírez-Vela; Luis Antonio Aguilar-Pérez; Juan Carlos Paredes-Rojas; Juan Alejandro Flores-Campos; Fernando ELi Ortiz-Hernández; Christopher René Torres-SanMiguel (MDPI AG, 2021)
This work presents a non-invasive methodology to obtain a three-dimensional femur model of three-year-old infants affected with Osteogenesis Imperfecta (OI) type III. DICOM® Files of a femur were processed to obtain a finite element model to assess the transverse, the oblique, and the comminuted fractures. The model is evaluated under a normal walking cycle. The loads applied were considered the most critical force generated on the normal walking cycle, and the analyses considered anisotropic bone conditions. The outcome shows stress concentration areas in the central zone of the diaphysis of the femur, and the highest levels of stress occur in the case of the comminuted fracture, while the transverse fracture presents the lowest values. Thus, the method can be helpful for determining the bone fracture behavior of certain pathologies, such as osteogenesis imperfecta, osteopenia, and osteoporosis.